Modelling and comparing two canopy shapes using FEM - Láng, Z.; Csorba, L. (International Journal of Horticultural Science, 2003)
Central leader and Vase form canopy models were built using FEM. Their main characteristics were chosen to be the same. The models were virtually exposed to the effect of steady-state horizontal forced vibration in the frequency range of 0-20 Hz. Acceleration-frequency curves were calculated and drawn to find the best frequency values for the effective detachment and also to see the acceleration differences in the limbs. For the same purpose the direction of shaking was also changed. It was found that for the Central leader canopy shape multidirectional shaking would bring uniform detachment while for the Vase form trees also the unidirectional shakers were appropriate. The acceleration achieved for the Vase form models were much higher than for the Central leader type. The acceleration-frequency curve of the shaker unit can be used to find the best frequency for shaking.